2012
DOI: 10.1002/jcp.23037
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise training increases APPL1 expression and improves insulin signaling in the hepatic tissue of diet‐induced obese mice, independently of weight loss

Abstract: Hepatic insulin resistance is the major contributor to fasting hyperglycemia in type 2 diabetes. The protein kinase Akt plays a central role in the suppression of gluconeogenesis involving forkhead box O1 (Foxo1) and peroxisome proliferator-activated receptor gamma co-activator 1 alpha (PGC-1α), and in the control of glycogen synthesis involving the glycogen synthase kinase beta (GSK3β) in the liver. It has been demonstrated that endosomal adaptor protein APPL1 interacts with Akt and blocks the association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 39 publications
10
82
1
7
Order By: Relevance
“…23 Moreover, chronic exercise increases APPL1 expression, which mediates exercise-induced increase of insulin action in the liver of diet-induced obese mice. 24 The results from the present study showed that in adiponectin-deficient mice, downregulation of APPL1 expression impaired insulin-induced vasodilatation, whereas augmented insulin-induced vasoconstriction. In addition, adiponectin treatment partly restored APPL1 expression, and thus reversed the imbalance between insulin-induced signaling in ySHRs and APN −/− mice.…”
supporting
confidence: 51%
“…23 Moreover, chronic exercise increases APPL1 expression, which mediates exercise-induced increase of insulin action in the liver of diet-induced obese mice. 24 The results from the present study showed that in adiponectin-deficient mice, downregulation of APPL1 expression impaired insulin-induced vasodilatation, whereas augmented insulin-induced vasoconstriction. In addition, adiponectin treatment partly restored APPL1 expression, and thus reversed the imbalance between insulin-induced signaling in ySHRs and APN −/− mice.…”
supporting
confidence: 51%
“…APPL1 downregulation is associated with GSK3beta phosphorylation decreased in liver of obese mice under fasting conditions. However, in response to endurance exercise training, these obese mice increased APPL1 expression, Akt/ APPL1 association, and GSK-3beta phosphorylation 23 , which corroborates our consideration above.…”
Section: Discussionsupporting
confidence: 89%
“…It is known that APPL1 can limit the interaction between Akt and TRB3 in mouse liver tissue, which is accompanied by an increase in the membrane translocation of APPL1, Akt activation, and enhancement in response to insulin stimulation 22,23 . Also, adiponectin also stimulates APPL1 in mouse hepatocyte cells with activation of another class of proteins, the p38 mitogen-activated protein kinases (p38MAPK), which activates glucose transporters protein.…”
Section: Discussionmentioning
confidence: 99%
“…This observation could be expected based on related literature (8,12,36,42) demonstrating insulin sensitizing actions of APPL1 in liver and skeletal muscle. Indeed, APPL1 levels were significantly decreased in endothelium of Zucker diabetic fatty rats (38), and a recent study suggested that chronic exercise in mice increased hepatic APPL1 expression, which, at least in part, accounted for improved insulin sensitivity (28). However, in a human study, there was higher APPL1 expression in type 2 diabetic muscle, and weight loss in these individuals was associated with reduced skeletal muscle APPL1 level (22).…”
Section: E801mentioning
confidence: 99%